Customer Experience, E-Service Quality, and Loyality in Online Food Delivery: The Case of Mie Gacoan - Nurwansyah, Alvin; Hartoyo; Suharjo, Budi (School of Business, IPB University (SB-IPB), 2025)
Background: The increasing popularity of online food delivery (OFD) services has prompted many restaurants, including Mie Gacoan, to adopt these platforms. However, in practice, Mie Gacoan frequently encounters customer complaints regarding order discrepancies when placing orders through various OFD platforms.Purpose: This study aims to analyze the factors contributing to customer complaints by examining customer experience and customer satisfaction, particularly in minimizing order discrepancies in online food delivery services. By understanding these factors, Mie Gacoan can enhance customer loyalty while maintaining a positive brand image on the OFD platforms it utilizes.Design/methodology/approach: This study employs a non-probability voluntary sampling method, successfully gathering data from 173 qualified respondents to ensure validity. A descriptive analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM) approach are used to test the hypotheses, allowing for the evaluation of multiple relationships among the variables within the research model.Findings/Result: The findings indicate that customer experience and e-service quality significantly influence customer satisfaction, which in turn impacts customer loyalty. The study emphasizes that strengthening customer loyalty requires first enhancing customer satisfaction by improving problem-solving mechanisms within the customer experience and refining compensation policies in e-service quality.Conclusion: The results highlight that customer satisfaction plays a crucial mediating role in fostering customer loyalty, as customer experience and e-service quality exert a stronger influence on satisfaction than on loyalty.Originality/value (State of the art): This study contributes to the existing literature by providing empirical insights into the role of customer experience and e-service quality in shaping customer satisfaction and loyalty in the online food delivery sector. The findings offer practical recommendations for service providers to improve their operational strategies and enhance customer retention. Keywords: customer experience, customer satisfaction, customer loyalty, e-service quality, online food delivery